Left brain, right stuff . how leaders make winning decisions . - Rosenzweig, Philip M. 1955-; Rosenzweig, Philip M. (London. Profile Book LTD., 2014)
"A renowned business expert examines decision-making in critical, big-time situations where the outcome shapes the destiny of companies, countries, sports teams, political campaigns, or the military Left Brain, Right Stuff is the book about decision making that takes off where others-Thinking, Fast and Slow, Predictably Irrational, and Decisive-leave off. It captures the essence of real-world decisions, where success only comes to those with the wisdom to push boundaries. The great paradox is that while we know a great deal about how we make routine decisions-from the way shoppers pick a box of cereal to how investors buy or sell-we know little about the most complex and consequential decisions of all-for example, whether to start a company, manage the risks of a business, or bid for a project and bring it to a successful completion. We need a new paradigm for situations where uncertainty reigns, rivalry is intense, and positive thinking matters. With compelling examples from business, sports, politics, and more, Phil Rosenzweig shows how high performance calls for a combination of skills: the need for careful analytical thinking-left brain-as well as the ability to take bold action-the right stuff"--
"The great paradox is that while we know a great deal about how we make routine decisions--from the way shoppers pick a box of cereal to how investors buy or sell--we know little about the most complex and consequential decisions of all--for example, whether to start a company, manage the risks of a business, or bid for a project and bring it to a successful completion. We need a new paradigm for situations where uncertainty reigns, rivalry is intense, and positive thinking matters. With compelling examples from business, sports, politics, and more, Phil Rosenzweig shows how high performance calls for a combination of skills: the need for careful analytical thinking--left brain--as well as the ability to take bold action--the right stuff"--
Paper Cover.
Includes bibliographical references (pages 287-301) and index.
Keywords: Rosenzweig, Philip M; Decision making; Decision making -- Psychological aspects; Leadership -- Psychological aspects; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; PSYCHOLOGY / Cognitive Psychology; SELF-HELP / Personal Growth / Success